The utility category subjacent in the Mathematical Education tendencies: a debate from the Historical-Critical Pedagogy (Research, Society and Development, 2021)
The present research, bibliographical nature, sets forth a debate on the category utility in the circle of Mathematics Educations Studies, in special in the Historical-Critical Pedagogy. As from, the research problem emerges from the following question: How is utility category understood in the circle of Mathematics Education Studies from the Historical-Critical Pedagogy views? Thus, the objective was to understand the utility category in the fields of Mathematics Educations Studies, in special, from the theoretical-methodological basis that are underlined in the Historical-Critical Pedagogy. First of all, we analyzed the referred tendency and its possible implications in the Mathematical Education. We checked that the utility is not learned in an immediate way, but by its relation that has its expression as an individual-society-human gender. So, the referred Pedagogy has contraposition with others, with pragmatical and utilities views, which undergoes within a conception that the mathematical knowledge has an essence linked to the immediacies of the current life. Through this understanding, there is a risk in transforming the Mathematics to a science that only incurs into validity because its simple practical immediacies applications, turning them into a true criterion of the math concepts. As implications, the Mathematic teaching has to be as criteria, the application and the direct relationship with the students currently life. Therefore, we understand that is necessary and urgent a debate that, mainly, takes into account the genesis and the historical development of the mathematical knowledge from the dialectical-materialist approach. The intention is to instigate the debate on the objectives and improve the development of the pedagogical praxis which has as foundation in an omni-lateral human formation.